Seizing the opportunity / Roslilee Ab. Halim … [et al.] - Ab. Halim, Roslilee; Sabar, Sarinah; Azis, Saflina; Zur, Rohana; Ab. Wahab, Norailis (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2020)
Opportunity identification involves technical expertise, such as financial analysis and market research and creativity, team building, problem-solving, and leadership. It was ticking off most of the factors, Infinitus Technology Sdn. Bhd. (ITSB) has identified the business opportunities, from upgrading the company's ownership status (from a partnership to private limited) to doing networking and joint ventures to seize more significant business opportunities. Starting up with HS Communication Enterprise in 2010, a partnership company that is formed by two nascent entrepreneurs who had gained their experience in communication systems by working for a major company, they incorporated the company to ITSB by 2012. The company is growing steadily, at around 15% annually since then. Being in a niche market of satellite communication and remote sensing, ITSB moves forward by creating and seizing business opportunities via a joint venture and business diversification. The achievement to immediately seize an opportunity brings a benefit that helps the company to succeed.